Phrenic Nerve Pacing Via Intramuscular Diaphragm Electrodes in Tetraplegic Subjects - DiMarco, Anthony F.; Onders, Raymond P.; Ignagni, Anthony; Kowalski, Krzysztof E.; Mortimer, J. Thomas (Chest, 2005)
Diaphragm pacing in ventilator-dependent tetraplegic subjects is usually achieved by the placement of phrenic nerve electrodes via thoracotomy. However, this technique may be accomplished less invasively via laparoscopic placement of IM electrodes, at a lower cost and with less risk of injury to the phrenic nerve. To assess the feasibility of laparascopic placement of IM diaphragm electrodes to achieve long-term ventilatory support in ventilator-dependent tetraplegic subjects. Two IM diaphragm electrodes were placed laparoscopically in each hemidiaphragm in five subjects with ventilator-dependent tetraplegia. Studies were performed either on an outpatient basis or with a single overnight hospitalization. Ventilator-dependent tetraplegic subjects were identified in whom bilateral phrenic nerve function was present, as determined by phrenic nerve conduction studies. Following electrode placement, subjects participated in a conditioning program to improve the strength and endurance of the diaphragm over a period of 15 to 25 weeks. The duration of the study was variable depending on the time necessary to determine the maximum duration that individuals could be maintained without mechanical ventilation support. Magnitude of inspired volume generation and duration of ventilatory support with bilateral diaphragm pacing alone. In four of the five subjects studied, initial bilateral diaphragm stimulation resulted in inspired volumes between 430 and 1,060 mL. Reconditioning of the diaphragm over several weeks resulted in substantial increases in inspired volumes to 1,100 to 1,240 mL. These subjects were comfortably maintained without mechanical ventilatory support for prolonged time periods by diaphragm pacing, by full-time ventilatory support in three subjects, and 20 h per day, in the fourth subject. No response to stimulation was observed in one subject, most likely secondary to denervation atrophy. Diaphragm pacing in ventilator-dependent tetraplegic subjects can be successfully achieved via laparascopic placement of IM electrodes.